Modulatory Effects of Probiotics During Pathogenic Infections With Emphasis on Immune Regulation - Raheem, Abdul; Liang, Lin; Zhang, Guangzhi; Cui, Shangjin (Frontiers in Immunology, 2021)
Currently, antibiotics are the main therapeutic agent used to combat bacterial infections, both in animals and humans. However, due to the massive and inappropriate use of antibiotics, antibiotic-resistant bacteria, even super bugs, have emerged during the past several years, and greatly compromise the efficacy of antibiotics. Thus, the development of new antibiotics is necessary, while the search for antibiotic alternatives continues. Probiotics are considered the ideal antibiotic substitute; in recent years, probiotic research concerning their application during pathogenic infection, with emphasis on modulating the immune system of the host, has been attracting considerable interest. Hence, the adverse effects of antibiotics and remedial effects of probiotics during infectious diseases have become central points of focus among researchers. Probiotics are live microorganisms; when given in adequate quantities, they augment and bestow good health effects to the host through different mechanisms. Among them, the regulation of host immune response during pathogenic infections is one of the most important mechanisms. A number of studies have investigated different aspect of probiotics. In this review, we mainly summarize recent discoveries and discuss two important aspects: 1) the applications of probiotics during pathogenic infections; and 2) their modulatory effects on the host immune response during infectious, as well as non-infectious diseases.